Pioglitazone abrogates testicular damage induced by testicular torsion/detorsion in rats - Mahmoud, Nevertyty Mohamed (Iran J Basic Med Sci, 2019)
OBJECTIVE(S): Testicular torsion/detorsion (T/D) is a well-known cause for infertility. Pioglitazone is an agonist of peroxisome proliferator activated receptor-gamma (PPAR-γ). Previous studies have shown that pioglitazone has anti-inflammatory, antioxidant and antiapoptotic properties. The present study hypothesized that pioglitazone may be protective against the testicular T/D tissue insults, and the possible pathophysiological mechanisms involved in this effect were also investigated. MATERIALS AND METHODS: Rats were randomly divided into four groups: sham group, T/D group where testicular torsion was performed for 4 hr followed by 4 hr of detorsion and two pioglitazone-treated groups (1 mg/kg and 3 mg/kg, by single intraperitoneal injection 30 min prior to detorsion). At the end of reperfusion period, blood, ipsilateral and contralateral testicular tissue samples were obtained for biochemical and histopathological examination. RESULTS: Pioglitazone reduced oxidative tissue damages, inflammatory mediators, and apoptotic markers and enhanced the total antioxidant status, and AMP-activated protein kinase level. Moreover, pioglitazone improved spermatogenesis evidenced by increased Johnsen’s score and reversed the histopathological damages induced by testicular T/D. The effects of pioglitazone were higher with the dose of 3 mg/kg. CONCLUSION: Pioglitazone exhibited a protective effect against the deleterious actions of testicular T/D. This beneficial potential of pioglitazone may be attributed to its antioxidant, anti-inflammatory and antiapoptotic properties, which was more obvious with the dose of 3 mg/kg. Pioglitazone may be a promising therapy for testicular T/D.